The Impact of The Indosiar Kisah Nyata Series on Housewives’ Perspective in Viewing Disharmony Family - Ade Irfan Abdurahman; Ukon Furkon Sukanda; Nur Musvita Sari; Dena Prisila; Ahmad Aji Azhari; Daniel Antoini NR (INJECT (Interdisciplinary Journal of Communication), 2022)
At the beginning development of Cultivation Theory a study of the impact of television on the audience, especially on violence impact. But in the development, cultivation theory has been successfully tested in other themes out of violence theme. One of the important findings from cultivation theory is heavy viewers' belief in the world, their perspective is reality appropriate to what they watch on television. The research is telling about the impact of watching the Kisah Nyata series on understanding disharmony in the family. With this quantity method, we argue with the hypothesis that watcher Kisah Nyata series will assume that reality of the disharmony family in the Kisah Nyata series is happening in real life, research results are showing that cultivation theory can be adapted to another theme from violence.